2019
DOI: 10.1101/789289
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cold exposure drives weight gain and adiposity following chronic suppression of brown adipose tissue

Abstract: Background and aim:Rodents are commonly housed below thermoneutrality and this exposure to 'cold' (i.e. 20°C) activates thermogenic brown (BAT) and beiging of white adipose tissue. Here, we examined whether a standard housing temperature (i.e. 20°C, a reduction in temperature of ~8°C) or YM-178, a highly-selective β 3-adrenoreceptor agonist, in obese animals raised at thermoneutrality, would impact differently on classical BAT or subcutaneous inguinal (IWAT) beige depots. Methods: Eighteen weanling Sprague-Daw… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 58 publications
0
4
1
Order By: Relevance
“…Intriguingly, both male and female animals housed at TN weighed significantly less than those at RT. This is in contrast to other studies observing increased body weight gain in rodents exposed to cold temperatures from either RT housing or TN housing (44,45). Some studies show no difference in body weight between rats housed at RT and TN (46), while others show increased diet-dependent adiposity at TN temperatures (47).…”
Section: Discussioncontrasting
confidence: 97%
“…Intriguingly, both male and female animals housed at TN weighed significantly less than those at RT. This is in contrast to other studies observing increased body weight gain in rodents exposed to cold temperatures from either RT housing or TN housing (44,45). Some studies show no difference in body weight between rats housed at RT and TN (46), while others show increased diet-dependent adiposity at TN temperatures (47).…”
Section: Discussioncontrasting
confidence: 97%
“…In line with data from chronic mild cold exposure (Aldiss et al . 2021), ICE increased BAT, eWAT and iWAT, but not liver mass (Fig. 2– J ), independent of diet, suggesting that the ICE‐induced increases in body mass were largely a result of increases in adiposity.…”
Section: Resultsmentioning
confidence: 92%
“…Importantly, acute exposure from 30°C to 14°C elicits AgRP neuron activity both rapidly and in a reversible manner (Deem et al 2020), suggesting that the effects of ICE we observed on energy intake and subsequently on body mass are not secondary to an extreme difference in ambient temperatures (30°C to 4°C). Likewise, Aldiss et al (2021) recently demonstrated that when obese rats, previously housed at 28°C, are chronically exposed to a mild ambient cold stress (21°C), they too exhibit increased weight gain and adipose tissue accumulation. As such, neither intermittent, nor chronic ambient cold exposure, regardless of whether it is mild or severe in nature, appears to be an efficacious treatment for obesity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, we have recently demonstrated that when mice are housed at thermoneutrality and their BAT phenotype is humanized, 25 a physiologically relevant model of ambient cold exposure causes rapid and persistent hyperphagia that exacerbates, rather than attenuates, diet‐induced obesity 26 . Similar reports are beginning to emerge 27 and thus it should be acknowledged that ambient cold exposure does not protect humanized rodents against diet‐induced obesity. As such, the identification of translationally relevant alternative treatment strategies is highly warranted.…”
Section: Introductionmentioning
confidence: 96%